Entropy effect of alkyl tails on phase behaviors of side-chain-jacketed polyacetylenes: Columnar phase and isotropic phase reentry. (22nd March 2016) - Liu, Xiaoqing; Wang, Jun; Yang, Shuang; Men, Yongfeng; Sun, Pingchuan; Chen, Er-Qiang
Abstract: We have investigated phase behaviors of a series of polyphenylacetylene derivatives, poly[di( n -alkyl) ethynylterephthalates] (P n, n is the number of carbon atoms of n -alkyl group, from 2 to 14), which are largely influenced by the length of n -alkyl tails on 2, 5-position of the phenyl group. With short alkyl groups ( n  ≤ 6), P n s form columnar liquid crystalline (Col) phases due to the "jacketing effect" of side-chains. As the alkyl tails become longer ( n  ≥ 8), an isotropic phase, which can be considered as a reentrant one (Ire ), is identified between lamellar phase (Lam) at low temperatures and Col phase at high temperatures. This unusual phase behavior is determined by the motional state of the side-chains. Thanks to in-situ variable temperature solid-state NMR experiments, the motion of main- and side-chains in different phases were distinguished, providing strong evidence for the entropy effect of side-chains which drives Ire and then Col phase inP n s ( n  ≥ 8) upon heating. Graphical abstract: Highlights: Alkyl tail length determines phase behavior of side-chain-jacketed polyacetylenes. Reentrant isotropic phase separates lamellar and columnar phases. Transition from reentrant isotropic to columnar phase is entropy driving.